The art of healing: Where personal reflections meet palliative care with Prof. Claudia Bausewein: Rozhovor s Prof. Claudií Bausewein (Paliativní medicína, 2025)
In a reflective conversation that goes beyond ordinary medical practice, Prof. Dr. med. Claudia Bausewein reveals her true devotion to palliative care since the very beginning of her career. She talks about her view of perfect happiness as living in tune with your inner self—being authentic, enjoying the healing power of nature, and forming real connections with others. Prof. Bausewein truly exemplifies a woman in her element; her work, deeply rooted in her values, shows that healing is as much about compassion as it is about science. This discussion invites us to see palliative medicine not only as a technical field but as a meaningful journey where every patient, every moment of relief, and every act of courage matters. Her inspiring words indeed leave a lasting impression.